Stress and the signs and symptoms of temporomandibular disorders a correlational study - Sembrano, Marilou H. (The Journal of the Philippine Dental Association)
Temporomandibular disorders are usually diagnosed based on their characteristics signs and symptoms which include pain, joint problems and altered mandibular function. These disorders are caused by many factors and stress has been implicated as one of the primary causes of these diseases. This study aimed to determine the relationship between stress and the occurrence of the signs and symptoms of the disease. Likewise, personal variables such as age, gender and marital status were related to the stress level. The data were gathered from the researcher's patient records. The results of the study showed that there was a slight positive correlation betwwn stress and the personal variables. There was a slight positive relationship between stress and the occurrence of pain and joint problems and a weak negative correlation between stress and altered mandibular function.